Sistem Informasi Pengolahan Data Atlet Bulu Tangkis Pada PB. Budi Surya Muara Enim ( Studi Kasus : PB. Budi Surya Muara Enim )”. - Sutruani, Leni; Suhartini, Suhartini; Fajriyah, Fajriyah (Jurnal Sistem Informasi, Teknik Informatika dan Teknologi Pendidikan, 2025)
The Badminton Athlete Data Processing Information System (BADPIS) is an application designed to assist management and coaches in managing and analyzing data related to badminton athletes. The aim of BADPIS is to improve information management and data-driven decision-making in the context of training, competition, and the development of badminton athletes. BADPIS features several key functionalities, including athlete profile management, recording match results, monitoring athlete physical condition and health, individual and team performance analysis, as well as training program planning. Data collected through BADPIS includes game statistics, injury history, training outcomes, and athlete performance development over time. Utilizing information and communication technology, BADPIS enables users to easily access and analyze data in real-time, both through computers and mobile devices. This allows coaches and management to make better-informed decisions in planning training programs, identifying areas for improvement, and monitoring athlete progress. In the context of badminton sports development, BADPIS can be a valuable tool in nurturing quality athletes, enhancing competitiveness at local, national, and international levels, and advancing the sport of badminton as a whole..